TANGGUNG JAWAB PENGANGKUTAN DALAM PERJANJIAN PENGANGKUTAN BARANG BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2008 - Sulaiman, Sulaiman; Dervia, Eli (JURNAL AKTA YUDISIA, 2024)
Law Number 17 of 2008, which regulates shipping, says that the carrier is responsible for the things that are transported under the terms of the contract. There are rules about the carrier's responsibility for lost or damaged goods during transport, and this study looks at how to settle arguments that come up because of those violations. The method used is normative research, and it looks at important legal articles and other parts of transportation law, such as the presumption-based liability principle. According to the study's results, the carrier is responsible for keeping the goods safe from the time they are received until they are delivered. However, he can avoid responsibility if he can show that the loss wasn't his fault. There are many rules that protect consumers, such as the Commercial Code and the Consumer Protection Law. Disputes can be settled in court or through other means.Keywords: Carrier's Liability, Contract of Carriage of Goods, Dispute Resolution, Transportation Law.